Procedure for the study and design of cold recycling with emulsion based on the monitoring and analysis of different projects - Miró Recasens , Rodrigo (2025)
The reuse of bituminous materials from worn pavements cannot be considered a new technique in road pavement maintenance and rehabilitation, since its use, in a more or less widespread manner, began in 1973 as a consequence of the oil crisis. In-place cold recycling, as an alternative to conventional milling and replacement, offers a series of well-known technical, economic, and environmental advantages.